Incidence of work stress on the work environment in the company DICOLAIC S.A. de Latacunga, year 2023 - Velásquez Beltrán, Alex Javier; Cajilema Tobar, Lisseth Paulina; González Ruiz, Luis Patricio (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Stress and work climate are two important factors in the organizational environment, as they determine patterns of conduct, behavior, performance and productivity. It’s important for organizations to study these variables with special emphasis on resource management, the most important of which is the human being, known as human capital. From the collected information, and according to the questionnaires and their scales, both standardized by international organizations and their professionals team, there are important results to explain some of the phenomena that is happening in the organizational environment, specifically in the company DICOLAIC S.A. in the city of Latacunga. In case of work stress, DIOLAIC S.A. has a low level of stress (60 pts.); on the other hand, in it’s individual evaluation, the area that presents an intermediate stress index is the Technological area (12 pts.). For the work climate evaluation, similar results were obtained, on average the organization is within the average standards of work climate (116, 31 pts.) being one of its areas to pay attention to the Job Stability (10,43 pts.) representing an indicator of low average work climate. In addition, through a correlational analysis between the two variables studied, it can be determined that the relationship between them is very weak, i.e. their relationship is very weak, with little influence of one variable on the other.